The borrowing of the English-language allusive neologisms as a strategy of Ukrainian media-discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article considers thematically the borrowings of the 1990-s – 2000-s’ English-language allusive neologisms; the author distinguishes between different types of allusion and analyses the role and place of such borrowings in the Ukrainian language.
Keywords: neologism; borrowing; historic allusion; philological allusion; double historic and philological allusion